Analisis Pengaruh Beban Operasional Pendapatan Operasional (BOPO) dan Loan to Deposit Ratio (LDR) Terhadap Capital Adequacy Ratio (CAR) pada PT. Bank Central Asia Tbk Periode Tahun 2019-2023 - Maria Christina; M. Djauhari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research examines the influence of the Operational Expense to Operational Income Ratio (BOPO) and Loan to Deposit Ratio (LDR) on the Capital Adequacy Ratio (CAR) at PT. Bank Central Asia Tbk. The hypothesis formulated in this study is that there is an effect of the Operational Expense to Operational Income Ratio (BOPO) on the Capital Adequacy Ratio (CAR) and an effect of the Loan to Deposit Ratio (LDR) on the Capital Adequacy Ratio (CAR) at PT. Bank Central Asia Tbk. Secondary data were collected over a period of 5 years or 60 months from 2019 to 2023. Data analysis was conducted using a descriptive quantitative approach with time series data utilizing regression analysis results. The findings of this study indicate that the Operational Expense to Operational Income Ratio (BOPO) has a significant and negative effect on the Capital Adequacy Ratio (CAR), while the Loan to Deposit Ratio (LDR) does not have a significant effect on the Capital Adequacy Ratio (CAR) at PT. Bank Central Asia